PENGEMBANGAN KARIER DAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN PRESTASI KERJA PEGAWAI PADA KANTOR CAMAT DENPASAR TIMUR - Artayasa, I Made; Sulandari, Sri (Universitas Wijaya Kusuma Surabaya, 2021)
Assessment of work performance needs to pay attention to career development and information technology. Career development shows future organizational development in line with capacity development for employees. Therefore, the researcher examines more deeply related to career development and information technology in an effort to improve the work performance of the employees of the East Denpasar District Office by using qualitative descriptive methods. Based on the analysis, it can be explained that (i) Career development acts as a motivation for the employees of the East Denpasar District Office to work maximum and optimally. (ii) Information technology plays a role in facilitating the completion of the work of the employees of the East Denpasar District Office because by utilizing computer technology it is able to facilitate data processing, information presentation and online work completion. (iii) Career development and information technology serve as tools to motivate and assist employees in achieving maximum work performance.Indicators of improving work performance are (i) Quality of work is indicated by the speed with employees provide population services to the community. (iii) The timing (pomptnees) is delayed when the electricity goes out so that the service is done manually which requires a longer service time compared to using online with computer power supported by the internet. (iii) Initiative (initiative) is shown by every employee who works based on their respective duties and responsibilities so that to complete the work they do not depend on their superiors or leaders. (iv) Capability still needs coaching and training for employees to be of higher quality and faster to provide services. (v) Communication (communication) is shown from the cooperation carried out by employees in completing work and always discussing in dealing with problems that arise.Keywords: career development, job performance, dan information technology